Kritik Sosial Melalui Kesenian: Analisis Mahasiswa Universitas Trunojoyo Madura dalam Konteks Kontemporer - Hafiz Hermawan Wicaksono; Qoni'ah Nur Wijayani (Lembaga Pengembangan Kinerja Dosen, 2024)
Study of students at Trunojoyo University, Madura, to analyze how they use art as a tool to convey social criticism in a contemporary context. This research uses a qualitative approach with in-depth interviews, observations, and content analysis of students' artistic works such as fine art, theater, music, and literature. The results of the analysis show that students at Trunojoyo University, Madura, use art as a powerful form of social criticism, depicting various issues such as gender inequality, corruption, social injustice and environmental issues. Art among students is used as a means to increase social awareness, stimulate thinking and stimulate social change. In the current context, students utilize technological innovation and social media to expand the impact of social criticism, creating works of art that stimulate discussion and reflection in society and society in general. This study not only provides insight into how students at Trunojoyo University, Madura, use art as a tool for social criticism, but also illustrates how art can be a force for transformative change in facing the social challenges faced by contemporary society.